2005 International Symposium on Computational Intelligence in Robotics and Automation
DOI: 10.1109/cira.2005.1554335
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent Autonomous Navigation for Mobile Robots: Spatial Concept Acquisition and Object Discrimination

Abstract: An autonomous system able to construct its own navigation strategy for mobile robots is proposed. The navigation strategy is molded from navigation experiences (succeeding as the robot navigates) according to a classical reinforcement learning procedure. The autonomous system is based on modular hierarchical neural networks. Initially the navigation performance is poor (many collisions occur). Computer simulations show that after a period of learning the autonomous system generates efficient obstacle avoidance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
1

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 8 publications
0
26
0
1
Order By: Relevance
“…If this is not the case, the design is more complex. In general, it is observed that systems generate undesirable behaviors, e.g., cyclic trajectories, if attractive objects are eclipsed [7]. This is the case considered in this paper: a reactive autonomous navigation system for mobile robots without a target sensory field.…”
Section: Introductionmentioning
confidence: 99%
“…If this is not the case, the design is more complex. In general, it is observed that systems generate undesirable behaviors, e.g., cyclic trajectories, if attractive objects are eclipsed [7]. This is the case considered in this paper: a reactive autonomous navigation system for mobile robots without a target sensory field.…”
Section: Introductionmentioning
confidence: 99%
“…In [6], innovate neuron models provide the navigation system the capacity for learning spatial concepts. Target seeking and collision avoidance behaviors are incrementally associated with specific features of objects (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Each object has a particular color, denoting its respective class. Obstacles are considered repulsive objects while targets are attractive objects [2]. The robot model is shown in Fig.…”
Section: Robot Model and Controllermentioning
confidence: 99%
“…The robot interacts with the environment by distance, color and 3ŷ fish (t) refers to the desired output after applying the fisher labeling given by (4) • to +90 • ). Each position holds three sensors (for distance, color and contact perception) [2]. In this work, the robot model has 17 sensor positions, differing from [3].…”
Section: Robot Model and Controllermentioning
confidence: 99%
See 1 more Smart Citation